Gene expression profiling reveals new aspects of PIK3CA mutation in ERalpha-positive breast cancer: major implication of the Wnt signaling pathway. - Magdalena Cizkova (Public Library of Science (PLoS), 2010)
Background The PI3K/AKT pathway plays a pivotal role in breast cancer development and maintenance. PIK3CA, encoding the PI3K catalytic subunit, is the oncogene exhibiting a high frequency of gain-of-function mutations leading to PI3K/AKT pathway activation in breast cancer. PIK3CA mutations have been observed in 30% to 40% of ERα-positive breast tumors. However the physiopathological role of PIK3CA mutations in breast tumorigenesis remains largely unclear. Methodology/principal findings To identify relevant downstream target genes and signaling activated by aberrant PI3K/AKT pathway in breast tumors, we first analyzed gene expression with a pangenomic oligonucleotide microarray in a series of 43 ERα-positive tumors with and without PIK3CA mutations. Genes of interest were then investigated in 249 ERα-positive breast tumors by real-time quantitative RT-PCR. A robust collection of 19 genes was found to be differently expressed in PIK3CA-mutated tumors. PIK3CA mutations were associated with over-expression of several genes involved in the Wnt signaling pathway (WNT5A, TCF7L2, MSX2, TNFRSF11B), regulation of gene transcription (SEC14L2, MSX2, TFAP2B, NRIP3) and metal ion binding (CYP4Z1, CYP4Z2P, SLC40A1, LTF, LIMCH1). Conclusion/significance This new gene set should help to understand the behavior of PIK3CA-mutated cancers and detailed knowledge of Wnt signaling activation could lead to novel therapeutic strategies.